Praktik Pembuatan Molases Mineral Blok (MMB) Sebagai Pemenuhan Kebutuhan Mineral Ternak di Desa Mojotengah, Kecamatan Kedu, Kabupaten Temanggung - Indra Kurniawan; Siti Aisah; Ananda Maya Apriliana; Hafizha Shada Alya; Herlan Tri Gunawan; Arifa Amalia Suryaningtyas; Anggita Harsya Fahrezy; Putri Umala Sari; Dodi Muhammad Yusuf; Tri Nugroho Pamungkas (Inovasi Sosial : Jurnal Pengabdian Masyarakat, 2025)
This community service activity was conducted in Sawahan Hamlet, Mojotengah Village, Kedu District, Temanggung Regency, with the primary objective of enhancing the health and productivity of sheep through the introduction and production of mineral block molasses as supplementary feed. Mineral block molasses is a nutrient-rich feed supplement designed to meet the mineral requirements of ruminants, particularly sheep, which are often not fully met by conventional forage. The program was implemented using a participatory method, beginning with a lecture session that provided theoretical knowledge regarding the benefits, composition, and formulation of mineral block molasses. This was followed by an interactive discussion session in which participants, mainly local sheep farmers, were encouraged to share challenges and constraints they face in livestock feeding management. The facilitators then provided practical problem-solving approaches tailored to the local context. The final stage involved a hands-on demonstration of the step-by-step process of producing mineral block molasses, enabling participants to observe and practice directly. The results of this activity showed that participants not only gained new knowledge about the nutritional importance of mineral supplementation but also developed the practical skills necessary to independently produce mineral block molasses for their livestock. This is expected to improve feed efficiency, promote better animal health, and increase livestock productivity. Furthermore, the activity fostered community awareness of sustainable livestock management practices and the economic benefits of producing feed supplements locally. In conclusion, this program successfully empowered the local farming community with both theoretical and practical competencies in mineral block molasses production, contributing to improved livestock performance and farmer welfare. The continuation of such initiatives is recommended to ensure long-term adoption and optimization of livestock feeding practices in the region.